2002
DOI: 10.1016/s0304-3975(01)00206-7
|View full text |Cite
|
Sign up to set email alerts
|

Hard variants of stable marriage

Abstract: The Stable Marriage Problem and its many variants have been widely studied in the literature [6, 22, 15], partly because of the inherent appeal of the problem, partly because of the elegance of the associated structures and algorithms, and partly because of important practical applications, such as the National Resident Matching Program [20] and similar large-scale matching schemes. Here, we present the first comprehensive study of variants of the problem in which the preference lists of the participants are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
222
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(238 citation statements)
references
References 15 publications
2
222
1
5
Order By: Relevance
“…An instance of SMTI always admits a stable solution and it can be found in linear time [22]. Thus these components contribute no blocking edge.…”
Section: Called the Stable Marriage Problem With Ties And Incomplete mentioning
confidence: 99%
“…An instance of SMTI always admits a stable solution and it can be found in linear time [22]. Thus these components contribute no blocking edge.…”
Section: Called the Stable Marriage Problem With Ties And Incomplete mentioning
confidence: 99%
“…In [18] it is shown that the decision problem 'is the pair (m, w) stable?' for a given SMP instance with unacceptablity and ties is an NP-complete problem, even in the absence of unacceptability.…”
Section: Propositionmentioning
confidence: 99%
“…as few or as many singles as possible. Examples of practical applications include an efficient kidney exchange program [21] and the National Resident Matching Program 3 [18]. Maximizing cardinality garantuees that as many donors as possible will get a compatible donor and as many medical graduates as possible will get a position.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable matching problems occur naturally while matching people to posts [18], such as the allocation of residents to hospitals in the US [17], Canada [5], and Scotland [11]. Variants of the problem occur such as the allocation of groups of students to university accommodation [12], and hard variants have been identified and studied by Irving and Manlove [16]. The problem has also attracted the interest of the constraint programming community [4,7,9,8,14].…”
Section: Introductionmentioning
confidence: 99%